2020
DOI: 10.1111/eva.12915
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from bamboo‐eating pandas and their gut microbiome: Gut microbiome flow and applications

Abstract: The giant panda is one of the most endangered mammals in the world, and many studies have revealed their evolutionary adaptation to the local environment (e.g., dietary cellulose and cyanide) on the evidences from population genetics and their gut microbiome. Here, based on the results of our analysis of the giant panda gut microbiome, we concluded that instability and resilience are the two primary characteristics of the giant panda gut microbiome. This basic information may have an impact on giant panda cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…One of the main characteristics in the gut microbial functions of wild foraging Yunnan snub-nosed monkeys was the enrichment in genes coding for putative enzymes involved in the degradation of the cyanide compounds present in bamboo. A similar result had been found in our previous studies on bamboo-eating pandas [39] , [44] , [56] , [57] , which were historically distributed in the Yunnan region [38] . Thus, based on our previously published 57 metagenomes (19 CA (meat-eating carnivorans), 12 HE (herbivore) [58] , 10 OC (omnivorous carnivorans) [58] , and 10 GP (giant pandas) [39] , and 6 RP (red pandas) [39] ), we tested our second hypothesis, that the wild foraging (high bamboo shoot intake and not provided with supplemental food) population shared a putative functional convergence in the gut microbiome with the wild bamboo-eating pandas.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…One of the main characteristics in the gut microbial functions of wild foraging Yunnan snub-nosed monkeys was the enrichment in genes coding for putative enzymes involved in the degradation of the cyanide compounds present in bamboo. A similar result had been found in our previous studies on bamboo-eating pandas [39] , [44] , [56] , [57] , which were historically distributed in the Yunnan region [38] . Thus, based on our previously published 57 metagenomes (19 CA (meat-eating carnivorans), 12 HE (herbivore) [58] , 10 OC (omnivorous carnivorans) [58] , and 10 GP (giant pandas) [39] , and 6 RP (red pandas) [39] ), we tested our second hypothesis, that the wild foraging (high bamboo shoot intake and not provided with supplemental food) population shared a putative functional convergence in the gut microbiome with the wild bamboo-eating pandas.…”
Section: Resultssupporting
confidence: 90%
“…The majority of bamboo shoots have a high proportion of cyanide compounds [37] . The gut microbiomes of bamboo-eating pandas display a high proportion of specific Proteobacterial groups (e.g., Pseudomonas ), which were related to the detoxification of cyanide compounds in bamboos [39] , [44] . Thus, the significantly enriched abundance of these Proteobacterial genera (e.g., Pseudomonas , Comamonas , and Acinetobacter ) might be a response to bamboo shoot intake in the W population.…”
Section: Resultsmentioning
confidence: 99%
“…The gut microbiota is an important system that provides metabolic flexibility for the host, and is key to helping host adapt and shifting to fluctuating environments (Baniel et al, 2021). Recent studies also emphasized the importance of host‐associated microbes to wellbeing and conservation of threatened animals both in situ and ex situ (Wang et al, 2020; West et al, 2019; Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated that plant-eating insects (including InsectBam) and the bamboo-eating pandas might harbor similar gut microbial groups derived from their dietary plants, which might be caused by the special physiological characteristics of the host. Our previous studies speculated that the brief digestion time, short digestive tract, and fast intestinal peristalsis might lead to high concentrations of oxygen that select for the growth of aerobes and facultative anaerobes (e.g., Pseudomonadaceae from Proteobacteria) in giant pandas [12] , [45] . Therefore, we deduced that the relatively simple digestive system of herbivorous insects (e.g., Orthoptera and Lepidoptera) might lead to the presence of low levels of oxygen in their digestive systems [46] , [47] , which could result in the survival of or colonization by organisms from the microbiota of their herbivorous diet (including bamboos).…”
Section: Resultsmentioning
confidence: 99%